The Letters of Heloise and Abelard
XIX, 366 p.
Keywords: The letters of Heloise and Abelard will remain one of the great, romantic and intellectual documents of human civilization while they, themselves, are probably second only to Romeo and Juliet in the fame accrued by tragic lovers. Here for the first time in Mart Martin McLaughlin's edition is the complete correspendence with commentary.